2011
DOI: 10.1186/1471-2164-12-s3-s23
|View full text |Cite
|
Sign up to set email alerts
|

Genetic copy number variants in myocardial infarction patients with hyperlipidemia

Abstract: BackgroundCardiovascular disease is the chief cause of death in Taiwan and many countries, of which myocardial infarction (MI) is the most serious condition. Hyperlipidemia appears to be a significant cause of myocardial infarction, because it causes atherosclerosis directly. In recent years, copy number variation (CNV) has been analyzed in genomewide association studies of complex diseases. In this study, CNV was analyzed in blood samples and SNP arrays from 31 myocardial infarction patients with hyperlipidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…In addition, hyperlipidemia is associated with many other diseases such as myocardial infarction. For example, one study found several CNVs to have a link to myocardial infarction and hyperlipidemia [20]. Most of these studies were focused on specific CNVs or genes within CNV regions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, hyperlipidemia is associated with many other diseases such as myocardial infarction. For example, one study found several CNVs to have a link to myocardial infarction and hyperlipidemia [20]. Most of these studies were focused on specific CNVs or genes within CNV regions.…”
Section: Resultsmentioning
confidence: 99%
“…Further, CDH13 has been reportedly associated with adiponectin levels in several studies (Ling et al 2009; Jee et al 2010; Chung et al 2011; Aslibekyan et al 2012) including the GOLDN Study (Aslibekyan et al 2012 et al 2010). Besides, CDH13 has also found associated with BMI, coronary artery disease, hypertension, myocardial infarction, dyslipidemia and metabolic syndrome (Fox et al 2007; Wellcome Trust Case Control Consortium 2007; Org et al 2009; Shia et al 2011; Fava et al 2011). Again, this locus for NHDL response to PPL needs to be reconfirmed among independent cohorts though this phenotype was even rarely measured in interventional studies.…”
Section: Discussionmentioning
confidence: 98%
“…CNVs are a significant source of genetic diversity, but their influence on disease susceptibility remains poorly understood. For cardiovascular disease, several studies on CNVs in myocardial infarction and hyperlipidaemia patients have been reported10; however, there has been no CNV research for coronary artery disease and metabolic comorbidity. In the present study, we compared the genomic DNA in the CAP and IMA from patients with coronary artery disease and metabolic comorbidity using array-CGH.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of CNVs in coronary artery disease have typically used DNA isolated from peripheral blood, and inconclusive results were obtained891011. The most pronounced genomic imbalance in patients with coronary artery disease and metabolic comorbidity are possibly detected in the target disease organs, such as coronary arteries.…”
mentioning
confidence: 99%